Expenditures among young adults with acute lymphoblastic leukemia by site of care. Issue 11 (19th January 2021) - Wolfson, Julie A.; Bhatia, Smita; Ginsberg, Jill; Becker, Laura K.; Bernstein, David; Henk, Henry J.; Lyman, Gary H.; Nathan, Paul C.; Puccetti, Diane; Wilkes, Jennifer J.; Winestone, Lena E.; Kenzik, Kelly M.
Abstract : Background: Individuals diagnosed with acute lymphoblastic leukemia (ALL) between the ages of 22 and 39 years experience worse outcomes than those diagnosed when they are 21 years old or younger. Treatment at National Cancer Institute–designated Comprehensive Cancer Centers (CCC) mitigates these disparities but may be associated with higher expenditures. Methods: Using deidentified administrative claims data (OptumLabs Data Warehouse), the cancer‐related expenditures were examined among patients with ALL diagnosed between 2001 and 2014. Multivariable generalized linear model with log‐link modeled average monthly health‐plan–paid (HPP) expenditures and amount owed by the patient (out‐of‐pocket [OOP]). Cost ratios were used to calculate excess expenditures (CCC vs non‐CCC). Incidence rate ratios (IRRs) compared CCC and non‐CCC monthly visit rates. Models adjusted for sociodemographics, comorbidities, adverse events, and months enrolled. Results: Clinical and sociodemographic characteristics were comparable between CCC (n = 160) and non‐CCC (n = 139) patients. Higher monthly outpatient expenditures in CCC patients (15, 792 vs 6404; P < .001) were driven by outpatient hospital HPP expenditures. Monthly visit rates and per visit expenditures for nonchemotherapy visits (IRR = 1.6; P = .001; CCC = 8247, non‐CCC = 1191) drove higher outpatient hospital expenditures among CCCs. Monthly OOP expenditures were higher at CCCs for outpatient care ( P = .02). Inpatient HPP expenditures were significantly higher at CCCs (25, 918 vs 13, 881; ꞵ = 0.9; P < .001) before accounting for adverse events but were no longer significant after adjusting for adverse events (ꞵ = 0.4; P = .1). Hospitalizations and length of stay were comparable. Conclusions: Young adults with ALL at CCCs have higher expenditures, likely reflecting differences in facility structure, billing practices, and comprehensive patient care. It would be reasonable to consider CCCs comparable to the oncology care model and incentivize the framework to achieve superior outcomes and long‐term cost savings. Lay Summary: Health care expenditures in young adults (aged 22‐39 years) with acute lymphoblastic leukemia (ALL) are higher among patients at National Cancer Institute‐designated Comprehensive Cancer Centers (CCC) than those at non‐CCCs. The CCC/non‐CCC differences are significant among outpatient expenditures, which are driven by higher rates of outpatient hospital visits and outpatient hospital expenditures per visit at CCCs. Higher expenditures and visit rates of outpatient hospital visits among CCCs may also reflect how facility structure and billing patterns influence spending or comprehensive care. Young adults at CCCs face higher inpatient HPP expenditures; these are driven by serious adverse events. Abstract : Young adults aged 22 to 39 years with acute lymphoblastic leukemia who are treated at a National Cancer Institute–designated Comprehensive Cancer Center (CCC) have higher expenditures than non‐CCC patients. Outpatient hospital monthly visit rates and per‐visit expenditures account for higher outpatient expenditures at CCCs. Inpatient expenditures are driven by serious adverse events.